ENVIRONMENTAL AND LEGAL PRIORITIES OF KAZAKHSTAN, RUSSIA AND BELARUS - Bogolyubov Сергей Александрович (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2013)
The scientific support for the form and content of environmental and legal interests of Kazakhstan, Russia and Belarus, organizations are environmental management and environmental protection is to be conducted, scientific study of combining economic and environmental interests of the society, where the role of the law increases.